Perancangan dan Implementasi Sistem Informasi Salon Kecantikan Berbasis Website untuk Efisiensi Layanan - Nisa Aulia; Binastya Anggara Sekti (Prosiding SISFOTEK, 2025)
This research aims to design a website-based information system to improve operational efficiency and service quality at Shella Beauty Salon. The development process uses the prototype method, including communication, quick planning, modeling, building the prototype, and evaluation. Testing was conducted using black box testing to ensure system functionality. The system was built using HTML, PHP, and MySQL database with features such as service management, online ordering, automatic reporting, and home service booking. The results show that the system helps streamline services, reduce recording errors, and assist both customers and administrators in managing transactions efficiently. The system is expected to strengthen Shella Beauty Salon’s competitiveness in the digital era.